The Measurement of External Accounts - Adler, Gustavo; Garcia-Macia, Daniel; Krogstrup, Signe (Washington, D.C. : International Monetary Fund, 2019)
Growing international integration in trade and finance can challenge the measurement of external accounts. This paper presents a unified conceptual framework for identifying sources of mismeasurement of foreign investment income in current account balances. The framework allows to derive a precise definition of measurement distortions and an empirical strategy for estimating their importance. As an application, we empirically estimate two specific distortions related to inflation and retained earnings on portfolio equity for a broad set of countries. We find these may explain a non-trivial share of current account imbalances and that they are particularly relevant in countries with large external investment positions. We also discuss how merchanting and profit-shifting activities could lead to measurement distortions. We suggest areas for future research and underline the need to strengthen data collection efforts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet